Sosialisasi Peracangan Kandang Kambing Berbasis GAHP di Desa Sampecita Kecamatan Kutalimbaru Kabupaten Deli Serdang - Dara Wisdianti; Purwo Siswoyo; Ida Khairani Siregar; Hendra Fahruddin Siregar (Arsil Media, 2023)
Al Amin Science and Industrial Park (Living Lab) is an area projected to become a center for field laboratories and workshops that accommodate all study programs at UNPAB. This area is also planned to be an Ecotourism. One of the functions that will be developed in this area is the livestock area. Facing the AEC (ASEAN Economic Community) 2015 in the field of food, especially livestock products in particular, strict standardization is needed so the concept of Good Animal Husbandry Practices (GAHP) needs to be applied. Thus, it is necessary to plan the concept of a livestock drive in the Al Amin Science and Industrial Park (Living Lab) livestock area by considering GAHP (Good Anima Husbandry Practice). The application of GAHP aims to ensure that the livestock products produced are safe for consumption with the right quality and suitable for consumers, while also ensuring that livestock products are produced in the right way without causing harm to the environment, health, safety, and welfare of workers in the livestock sector. The purpose of this research is to produce a design of supporting buildings in the Al Amin Science and Industrial Park (Living Lab) livestock area based on GAHP. The results of this design are expected to be a direction for the development of supporting buildings in the livestock area of the Al Amin Science and Industrial Park (Living Lab)